Clinical diversity and treatment approaches to blastic plasmacytoid dendritic cell neoplasm: a retrospective multicentre study. (10th March 2020) - Brüggen, M.‐C.; Valencak, J.; Stranzenbach, R.; Li, N.; Stadler, R.; Jonak, C.; Bauer, W.; Porkert, S.; Blaschke, A.; Meiss, F.; Nicolay, J. P.; Wehkamp, U.; et al.
Abstract: Background: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare, aggressive type of haematologic precursor malignancy primarily often manifesting in the skin. We sought to provide a thorough clinical characterization and report our experience on therapeutic approaches to BPDCN. Methods: In the present multicentric retrospective study, we collected all BPDCN cases occurring between 05/1999 and 03/2018 in 10 secondary care centres of the German–Swiss–Austrian cutaneous lymphoma working group. Results: A total of 37 BPDCN cases were identified and included. Almost 90% of the patients had systemic manifestations (bone marrow, lymph nodes, peripheral blood) in addition to skin involvement. The latter presented with various types of cutaneous lesions: nodular (in more than 2/3) and bruise‐like (in 1/3) skin lesions, but also maculopapular exanthema (in circa 1/6). Therapeutically, 22 patients received diverse combinations of chemotherapeutic regimens and/or radiotherapy. Despite initial responses, all of them ultimately relapsed and died from progressive disease. Eleven patients underwent haematopoietic stem cell transplantation (HSCT; autologous HSCT n = 3, allo‐HSCT n = 8). The mortality rate among HSCT patients was only 33.33% with a median survival time of 60.5 months. Conclusion: Our study demonstrates the clinical diversity of cutaneous BPDCN manifestations and the positive development observed after the introduction of HSCT.